Outlier Removal Technique for Estimating Link Travel Times Using DSRC Probes - Jang, Jinhwan (IJRDO -Journal of Computer Science Engineering, 2017)
Abstract- As electronic toll collection systems based on 5.8 GHzdedicated short-range communications (DSRC) have become popular,real-life travel time collection via DSRC systems is attracting moreinterest. The DSRC system, composed of an on-board unit and a roadsideunit, has the advantage of gathering section travel times directly.However, outliers resulting from vehicles entering or exiting a section,parking activities, and so on have been considered a critical hurdle tobe overcome in estimating reliable travel times. In this study, a modifiedFerguson test is applied to clean DSRC probe data on a signalized ruralhighway in Korea. The proposed method was tested with 24-h blockreal-world data, indicating satisfactory results